1987
DOI: 10.1037/0022-0167.34.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three theoretically derived variables in predicting career and academic behavior: Self-efficacy, interest congruence, and consequence thinking.

Abstract: This study explored the differential contribution of three alternative theoretically based variables, self-efficacy, interest congruence, and consequence thinking, in explaining career-relevant behavior in students considering science and engineering fields. Results of multiple regression analyses indicated that self-efficacy was the most useful of the three in predicting grades and persistence in technical/scientific majors, both self-efficacy and congruence contributed to the prediction of range of perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
208
1
11

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(232 citation statements)
references
References 22 publications
12
208
1
11
Order By: Relevance
“…Self-efficacy has consistently been found to be associated with work related performance in numerous studies, including those of coping with difficult career-related tasks (Stumpf, Brief, & Hartman, 1987), career choice (Lent, Brown, & Larkin, 1987) and adaptability to new technology (Hill, Smith, & Mann, 1987). People with strong self-efficacy beliefs exert greater efforts to master a challenge while those with weak self-efficacy beliefs are likely to reduce their efforts or even quit (Bandura & Schunk, 1981;Brown & Inouyne, 1978;Schunk, 1981;Weinberg, Gould, & Jackson, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy has consistently been found to be associated with work related performance in numerous studies, including those of coping with difficult career-related tasks (Stumpf, Brief, & Hartman, 1987), career choice (Lent, Brown, & Larkin, 1987) and adaptability to new technology (Hill, Smith, & Mann, 1987). People with strong self-efficacy beliefs exert greater efforts to master a challenge while those with weak self-efficacy beliefs are likely to reduce their efforts or even quit (Bandura & Schunk, 1981;Brown & Inouyne, 1978;Schunk, 1981;Weinberg, Gould, & Jackson, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…For example, student motivation and self-efficacy are important variables related to levels of engagement with university study (Lecompte et al, 1983;Ramsden, 2003). Regression analysis performed by Lent et al (1987) showed self-efficacy to be the most significant factor in predicting retention and academic performance. First-year students who attribute negative academic events to specific, unreliable, external causes generally receive higher grades than those who attribute negative events to stable internal causes (Peterson & Barrett, 1987), while students with motivation and an internal locus of control typically respond more positively to university (Fazey & Fazey, 2001).…”
Section: Student Engagement: Predictors Of Successmentioning
confidence: 99%
“…Studies have shown that self-efficacy is able to predict a university student's persistence in science majors as well as science career choices [9,10,13,14,16]. Additionally, researchers have found that self-efficacy can predict achievement in science for high school students [24,25] and university students [8][9][10][11][12]. At Florida International University, an hispanic-serving institution in the southeastern United States, we have also found that a student's self-efficacy in physics at the beginning of an introductory physics course predicts the likelihood of a student passing that same course [26].…”
Section: Previous Research On the Development Of Self-efficacymentioning
confidence: 99%
“…Since the 1980s an abundance of research has shown that science self-efficacy, or confidence in one's own ability to complete the actions necessary to perform a task [7], is related to success in particular fields [8][9][10][11][12], as well as a predictor of the career choice an individual will make [10,[13][14][15][16]. A few researchers in physics education have also shown a link between physics self-efficacy and success [17][18][19].…”
Section: Introductionmentioning
confidence: 99%